Preparation method and application of asphalt concrete
By using specific proportions of raw materials and process treatment in asphalt concrete, the thermal conductivity, crack resistance and wear resistance of asphalt concrete are improved, the problem of poor performance coordination in the existing technology is solved, and the stability and durability of the product are improved .
Patent Information
- Application Number
- CN202411353072.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-09-26
AI Technical Summary
The wear resistance of existing asphalt concrete is poor, the thermal conductivity and crack resistance are difficult to coordinate, and the water and freezing resistance are insufficient, which limits the efficiency of the product.
Use a specific proportion of asphalt, cement, coarse aggregate, fine aggregate, fly ash and silane coupling agent, and improve the interface and performance coordination through the coordinated formulation of enhanced reinforcement and modified filler agent. , including the treatment of sheet talc powder, nano silicon carbide whiskers and kaolin modification liquid, and optimize the stirring process of raw materials.
It significantly improves the thermal conductivity, crack resistance and wear resistance of asphalt concrete, and improves the water, freezing and heat resistance of the product, achieving balance, coordination and stability of performance.
Smart Images

Figure BDA0005062849510000111 
Figure BDA0005062849510000121 
Figure BDA0005062849510000122
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of asphalt concrete, and in particular to a preparation method of asphalt concrete and application thereof. Background Art
[0002] Asphalt concrete mixture is an asphalt mixture that meets technical standards and is composed of mineral materials of prescribed grading, such as coarse aggregate, fine aggregate and filler in appropriate proportions, mixed with asphalt binder. Asphalt concrete is a composite material, usually used in roads, parking lots, airports, and the core of dams. It is made of mineral aggregate combined with asphalt, laid in layers, and compacted.
[0003] Existing asphalt concrete has poor wear resistance. At the same time, the thermal conductivity and crack resistance of asphalt concrete are difficult to balance and coordinate with the wear resistance. The product's water resistance, frost resistance and thermal stability are poor, which further limits the product's efficiency. Summary of the invention
[0004] In view of the defects of the prior art, the purpose of the present invention is to provide a method for preparing asphalt concrete and application thereof, so as to solve the problems raised in the above background technology.
[0005] The present invention solves the technical problem by adopting the following technical solution:
[0006] The present invention provides a method for preparing asphalt concrete, comprising the following steps:
[0007] Step 1: weigh the raw materials according to weight:
[0008] Asphalt 35-40 parts, cement 25-30 parts, coarse aggregate 10-15 parts, strength-enhancing agent 9-12 parts, fine aggregate 8-14 parts, modified filler 5-8 parts, fly ash 4-6 parts, silane coupling agent 3-5 parts, deionized water 30-35 parts;
[0009] Step 2, stirring and mixing the strengthening agent, modified filler, fly ash, silane coupling agent and deionized water at a speed of 450-550 r / min for 1-2 hours, and obtaining a mixed agent after the mixing is completed;
[0010] Step three, asphalt, cement, coarse aggregate, fine aggregate and mixing agent are stirred at a temperature of 110-120° C. for 2-3 hours, and the asphalt concrete of the present invention is obtained after the stirring is completed.
[0011] Preferably, the coarse aggregate is crushed stone with a particle size of 10 to 15 mm; the fine aggregate is fine sand with a particle size of 0.5 to 1.5 mm;
[0012] The fly ash is Class I fly ash; and the silane coupling agent is silane coupling agent KH560.
[0013] Preferably, the preparation method of the strengthening agent is:
[0014] S01: Stir and mix the flaky talc powder in a 5% potassium permanganate solution which is 3 to 5 times the total weight of the flaky talc powder, and then wash and dry;
[0015] S02: mixing dry flaky talc powder, phosphate buffer solution and carboxymethyl cellulose in a weight ratio of (4-6):(2-5):2 to obtain flaky talc liquid;
[0016] S03: Emphasis on the preparation of treatment agents:
[0017] The nano silicon carbide whiskers are mixed with a sufficient amount of sodium silicate solution to obtain a whisker solution, and 5 to 8 parts of the whisker solution, 3 to 5 parts of sodium lignin sulfonate solution, and 2 to 4 parts of lanthanum oxide are mixed and stirred to obtain a stress treatment agent;
[0018] S04: Mix the flaky talc liquid and the strengthening agent in a weight ratio of 5:(2-3) and perform ball milling at a ball milling speed of 1000-1500r / min for 2h. After the ball milling is completed, wash with water and dry to obtain the strengthening agent.
[0019] Preferably, the pH value of the phosphate buffer solution in S02 is 5.5;
[0020] The mass fraction of the sodium silicate solution in S03 is 2-5%; the mass fraction of the sodium lignin sulfonate solution is 3-6%.
[0021] Preferably, the average particle size of the nano-silicon carbide whiskers is 300-400 nm, and the aspect ratio of the whiskers is 20-30.
[0022] Preferably, the preparation method of the modified filler is:
[0023] S11: irradiating the silicon powder in a proton irradiation box for 5 to 10 minutes at an irradiation power of 350 to 400 W. After the irradiation, preheating the irradiated silicon powder at 55 to 60° C. for 10 minutes, and then heat-insulating the silicon powder to obtain pretreated silicon powder;
[0024] S12: adding the pretreated silicon powder to kaolin modification liquid which is 3 to 5 times the total amount of the pretreated silicon powder, stirring and modifying the liquid, after the stirring is completed, filtering and drying to obtain a modified filler.
[0025] Preferably, the stirring speed of the stirring modification treatment is 550 to 750 r / min, and the stirring time is 45 to 55 min.
[0026] Preferably, the preparation method of kaolin modified liquid is:
[0027] Add 4 to 7 parts of kaolin and 1 to 3 parts of yttrium nitrate solution into 5 to 8 parts of sodium citrate solution, then add 2 to 3 parts of silane coupling agent KH550 and 2 to 4 parts of boron nitride, stir and mix thoroughly to obtain kaolin modified liquid.
[0028] Preferably, the mass fraction of the sodium citrate solution is 5-8%; the mass fraction of the yttrium nitrate solution is 2-5%.
[0029] The invention also provides an application of a method for preparing asphalt concrete in road paving.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] The asphalt concrete of the present invention adopts asphalt and cement to blend coarse aggregate, fine aggregate and fly ash, and adds a silane coupling agent to improve the interface of the raw materials. The added strength-enhancing agent and modified filler are coordinated and coordinated to achieve synergistic effect. The thermal conductivity, crack resistance and wear resistance of the product are balanced and coordinated to improve, and the water resistance, frost resistance and thermal stability of the product are remarkable. In the preparation of the strength-enhancing agent, flaky talcum powder is subjected to potassium permanganate solution optimization and improvement treatment, and the added phosphate buffer solution and carboxymethyl cellulose are blended and coordinated to obtain flaky talcum liquid. At the same time, a strengthening treatment agent is used for coordination treatment. The nano silicon carbide whiskers in the strengthening treatment agent are in a whisker-like structure and are improved by sodium silicate solution treatment to improve the stability of the whisker structure. The sodium lignin sulfonate solution is used to improve the stability of the whisker structure. The liquid and lanthanum oxide are harmonized and coordinated, and the flaky talc system is further coordinated. The flaky talc system is matched with the whisker system and dispersed in the system to enhance the interface between the raw materials of the system, and at the same time improve the performance coordination and performance stability of the product; the modified filler adopts silicon powder after proton irradiation to stimulate its silicon powder activity efficiency, and then improves it through preheating, so as to better harmonize the kaolin modified liquid. The kaolin modified liquid adopts kaolin, yttrium nitrate solution, sodium citrate solution, silane coupling agent KH550 and boron nitride to coordinate. The boron nitride raw material is matched with the lamellar structure of kaolin, and the coordination between the raw materials is achieved, so that the modified filler and the strengthening agent have a stronger coordination effect, and the performance of the obtained product is further improved. DETAILED DESCRIPTION
[0032] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] A method for preparing asphalt concrete in this embodiment comprises the following steps:
[0034] Step 1: weigh the raw materials according to weight:
[0035] Asphalt 35-40 parts, cement 25-30 parts, coarse aggregate 10-15 parts, strength-enhancing agent 9-12 parts, fine aggregate 8-14 parts, modified filler 5-8 parts, fly ash 4-6 parts, silane coupling agent 3-5 parts, deionized water 30-35 parts;
[0036] Step 2, stirring and mixing the strengthening agent, modified filler, fly ash, silane coupling agent and deionized water at a speed of 450-550 r / min for 1-2 hours, and obtaining a mixed agent after the mixing is completed;
[0037] Step three, asphalt, cement, coarse aggregate, fine aggregate and mixing agent are stirred at a temperature of 110-120° C. for 2-3 hours, and the asphalt concrete of the present invention is obtained after the stirring is completed.
[0038] The coarse aggregate in this embodiment is crushed stone with a particle size of 10 to 15 mm; the fine aggregate is fine sand with a particle size of 0.5 to 1.5 mm;
[0039] The fly ash is Class I fly ash; and the silane coupling agent is silane coupling agent KH560.
[0040] The preparation method of the strengthening agent of this embodiment is:
[0041] S01: Stir and mix the flaky talc powder in a 5% potassium permanganate solution which is 3 to 5 times the total weight of the flaky talc powder, and then wash and dry;
[0042] S02: mixing dry flaky talc powder, phosphate buffer solution and carboxymethyl cellulose in a weight ratio of (4-6):(2-5):2 to obtain flaky talc liquid;
[0043] S03: Emphasis on the preparation of treatment agents:
[0044] The nano silicon carbide whiskers are mixed with a sufficient amount of sodium silicate solution to obtain a whisker solution, and 5 to 8 parts of the whisker solution, 3 to 5 parts of sodium lignin sulfonate solution, and 2 to 4 parts of lanthanum oxide are mixed and stirred to obtain a stress treatment agent;
[0045] S04: Mix the flaky talc liquid and the strengthening agent in a weight ratio of 5:(2-3) and perform ball milling at a ball milling speed of 1000-1500r / min for 2h. After the ball milling is completed, wash with water and dry to obtain the strengthening agent.
[0046] The pH value of the phosphate buffer solution in S02 of this embodiment is 5.5;
[0047] The mass fraction of the sodium silicate solution in S03 is 2-5%; the mass fraction of the sodium lignin sulfonate solution is 3-6%.
[0048] The average particle size of the nano-SiC whiskers in this embodiment is 300-400 nm, and the aspect ratio of the whiskers is 20-30.
[0049] The preparation method of the modified filler of this embodiment is:
[0050] S11: irradiating the silicon powder in a proton irradiation box for 5 to 10 minutes at an irradiation power of 350 to 400 W. After the irradiation, preheating the irradiated silicon powder at 55 to 60° C. for 10 minutes, and then heat-insulating the silicon powder to obtain pretreated silicon powder;
[0051] S12: adding the pretreated silicon powder to kaolin modification liquid which is 3 to 5 times the total amount of the pretreated silicon powder, stirring and modifying the liquid, after the stirring is completed, filtering and drying to obtain a modified filler.
[0052] The stirring speed of the stirring modification treatment in this embodiment is 550-750 r / min, and the stirring time is 45-55 min.
[0053] The preparation method of the kaolin modified liquid of this embodiment is:
[0054] Add 4 to 7 parts of kaolin and 1 to 3 parts of yttrium nitrate solution into 5 to 8 parts of sodium citrate solution, then add 2 to 3 parts of silane coupling agent KH550 and 2 to 4 parts of boron nitride, stir and mix thoroughly to obtain kaolin modified liquid.
[0055] The mass fraction of the sodium citrate solution in this embodiment is 5-8%; the mass fraction of the yttrium nitrate solution is 2-5%.
[0056] The present embodiment provides an application of a method for preparing asphalt concrete in road paving.
[0057] Example 1.
[0058] A method for preparing asphalt concrete in this embodiment comprises the following steps:
[0059] Step 1: weigh the raw materials according to weight:
[0060] Asphalt 35 parts, cement 25 parts, coarse aggregate 10 parts, strength-enhancing agent 9 parts, fine aggregate 8 parts, modified filler 5 parts, fly ash 4 parts, silane coupling agent 3 parts, deionized water 30 parts;
[0061] Step 2: Stir and mix the strengthening agent, modified filler, fly ash, silane coupling agent and deionized water at a speed of 450 r / min for 1 hour, and obtain a mixed agent after the mixing is completed;
[0062] Step three, asphalt, cement, coarse aggregate, fine aggregate and mixing agent are stirred at a stirring temperature of 110° C. for 2 hours, and the asphalt concrete of the present invention is obtained after the stirring is completed.
[0063] The coarse aggregate in this embodiment is crushed stone with a particle size of 10 mm; the fine aggregate is fine sand with a particle size of 0.5 mm;
[0064] The fly ash is Class I fly ash; and the silane coupling agent is silane coupling agent KH560.
[0065] The preparation method of the strengthening agent of this embodiment is:
[0066] S01: Stir and mix the flaky talc powder in a 5% potassium permanganate solution which is 3 times the total weight of the flaky talc powder, and then wash and dry;
[0067] S02: mixing dry flaky talc powder, phosphate buffer solution and carboxymethyl cellulose in a weight ratio of 4:2:2 to obtain flaky talc liquid;
[0068] S03: Emphasis on the preparation of treatment agents:
[0069] The nano silicon carbide whiskers are mixed with a sufficient amount of sodium silicate solution to obtain a whisker solution, and 5 parts of the whisker solution, 3 parts of sodium lignin sulfonate solution and 2 parts of lanthanum oxide are mixed and stirred to obtain a stress treatment agent;
[0070] S04: The flaky talc liquid and the strengthening agent are mixed in a weight ratio of 5:2 and ball-milled at a ball-milling speed of 1000 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water and dried to obtain a strengthening agent.
[0071] The pH value of the phosphate buffer solution in S02 of this embodiment is 5.5;
[0072] The mass fraction of the sodium silicate solution in S03 is 2%; the mass fraction of the sodium lignin sulfonate solution is 3%.
[0073] The average particle size of the nano-silicon carbide whiskers in this embodiment is 300 nm, and the aspect ratio of the whiskers is 20.
[0074] The preparation method of the modified filler of this embodiment is:
[0075] S11: irradiating the silicon powder in a proton irradiation box for 5 minutes at an irradiation power of 350 W. After the irradiation, preheating the irradiated silicon powder at 55° C. for 10 minutes and then heat-insulating the silicon powder to obtain pretreated silicon powder.
[0076] S12: adding the pretreated silicon powder to kaolin modification liquid in an amount three times the total amount of the pretreated silicon powder, stirring and modifying the liquid, and after the stirring is completed, filtering and drying to obtain a modified filler.
[0077] The stirring speed of the stirring modification treatment in this embodiment is 550 r / min, and the stirring time is 45 min.
[0078] The preparation method of the kaolin modified liquid of this embodiment is:
[0079] Add 4 parts of kaolin and 1 part of yttrium nitrate solution to 5 parts of sodium citrate solution, then add 2 parts of silane coupling agent KH550 and 2 parts of boron nitride, stir and mix thoroughly to obtain kaolin modified solution.
[0080] The mass fraction of the sodium citrate solution in this embodiment is 5%; the mass fraction of the yttrium nitrate solution is 2%.
[0081] The present embodiment provides an application of a method for preparing asphalt concrete in road paving.
[0082] Example 2.
[0083] A method for preparing asphalt concrete in this embodiment comprises the following steps:
[0084] Step 1: weigh the raw materials according to weight:
[0085] Asphalt 40 parts, cement 30 parts, coarse aggregate 15 parts, strength-enhancing agent 12 parts, fine aggregate 14 parts, modified filler 8 parts, fly ash 6 parts, silane coupling agent 5 parts, deionized water 35 parts;
[0086] Step 2: Stir and mix the strengthening agent, modified filler, fly ash, silane coupling agent and deionized water at a speed of 550 r / min for 2 hours, and obtain a mixed agent after the mixing is completed;
[0087] Step three, asphalt, cement, coarse aggregate, fine aggregate and mixing agent are stirred at a temperature of 120° C. for 3 hours, and the asphalt concrete of the present invention is obtained after the stirring is completed.
[0088] The coarse aggregate in this embodiment is crushed stone with a particle size of 15 mm; the fine aggregate is fine sand with a particle size of 1.5 mm;
[0089] The fly ash is Class I fly ash; and the silane coupling agent is silane coupling agent KH560.
[0090] The preparation method of the strengthening agent of this embodiment is:
[0091] S01: Stir and mix the flaky talc powder in a 5% potassium permanganate solution which is 5 times the total weight of the flaky talc powder, and then wash and dry;
[0092] S02: mixing dry flaky talc powder, phosphate buffer solution and carboxymethyl cellulose in a weight ratio of 6:5:2 to obtain flaky talc liquid;
[0093] S03: Emphasis on the preparation of treatment agents:
[0094] The nano silicon carbide whiskers are mixed with a sufficient amount of sodium silicate solution to obtain a whisker solution, and 8 parts of the whisker solution, 5 parts of sodium lignin sulfonate solution, and 4 parts of lanthanum oxide are mixed and stirred to obtain a stress treatment agent;
[0095] S04: Mix the flaky talc liquid and the strengthening agent in a weight ratio of 5:3 and perform ball milling at a ball milling speed of 1500r / min for 2h. After the ball milling is completed, wash with water and dry to obtain the strengthening agent.
[0096] The pH value of the phosphate buffer solution in S02 of this embodiment is 5.5;
[0097] The mass fraction of the sodium silicate solution in S03 is 5%; the mass fraction of the sodium lignin sulfonate solution is 6%.
[0098] The average particle size of the nano-silicon carbide whiskers in this embodiment is 400 nm, and the aspect ratio of the whiskers is 30.
[0099] The preparation method of the modified filler of this embodiment is:
[0100] S11: irradiating the silicon powder in a proton irradiation box for 10 minutes at an irradiation power of 400 W. After the irradiation is completed, preheating the irradiated silicon powder at 60° C. for 10 minutes and then heat-insulating the silicon powder to obtain pretreated silicon powder;
[0101] S12: adding the pretreated silicon powder to kaolin modification liquid which is 5 times the total amount of the pretreated silicon powder, stirring and modifying the liquid, after the stirring is completed, filtering and drying to obtain a modified filler.
[0102] The stirring speed of the stirring modification treatment in this embodiment is 750 r / min, and the stirring time is 55 min.
[0103] The preparation method of the kaolin modified liquid of this embodiment is:
[0104] 7 parts of kaolin and 3 parts of yttrium nitrate solution were added to 8 parts of sodium citrate solution, and then 3 parts of silane coupling agent KH550 and 4 parts of boron nitride were added, and the mixture was stirred and mixed to obtain a kaolin modified solution.
[0105] The mass fraction of the sodium citrate solution in this embodiment is 8%; the mass fraction of the yttrium nitrate solution is 5%.
[0106] The present embodiment provides an application of a method for preparing asphalt concrete in road paving.
[0107] Example 3.
[0108] A method for preparing asphalt concrete in this embodiment comprises the following steps:
[0109] Step 1: weigh the raw materials according to weight:
[0110] 37.5 parts of asphalt, 27.5 parts of cement, 12.5 parts of coarse aggregate, 10 parts of bonding agent, 11 parts of fine aggregate, 6.5 parts of modified filler, 5 parts of fly ash, 4 parts of silane coupling agent, and 32.5 parts of deionized water;
[0111] Step 2: Stir and mix the strengthening agent, modified filler, fly ash, silane coupling agent and deionized water at a speed of 500 r / min for 1.5 hours, and obtain a mixed agent after the mixing is completed;
[0112] Step three, asphalt, cement, coarse aggregate, fine aggregate and mixing agent are stirred at a stirring temperature of 15° C. for 2.5 hours, and the asphalt concrete of the present invention is obtained after the stirring is completed.
[0113] The coarse aggregate in this embodiment is crushed stone with a particle size of 12.5 mm; the fine aggregate is fine sand with a particle size of 1.0 mm;
[0114] The fly ash is Class I fly ash; and the silane coupling agent is silane coupling agent KH560.
[0115] The preparation method of the strengthening agent of this embodiment is:
[0116] S01: Stir and mix the flaky talc powder in a 5% potassium permanganate solution which is 4 times the total weight of the flaky talc powder, and then wash and dry;
[0117] S02: mixing dry flaky talc powder, phosphate buffer solution and carboxymethyl cellulose in a weight ratio of 5:3.5:2 to obtain flaky talc liquid;
[0118] S03: Emphasis on the preparation of treatment agents:
[0119] The nano silicon carbide whiskers are mixed with a sufficient amount of sodium silicate solution to obtain a whisker solution, and 6.5 parts of the whisker solution, 4 parts of sodium lignin sulfonate solution, and 3 parts of lanthanum oxide are mixed and stirred to obtain a stress treatment agent;
[0120] S04: Mix flaky talc and strengthening agent in a weight ratio of 5:2.5 and perform ball milling at a ball milling speed of 1250r / min for 2h. After the ball milling is completed, wash with water and dry to obtain a strengthening agent.
[0121] The pH value of the phosphate buffer solution in S02 of this embodiment is 5.5;
[0122] The mass fraction of the sodium silicate solution in S03 is 3.5%; the mass fraction of the sodium lignin sulfonate solution is 4.5%.
[0123] The average particle size of the nano-silicon carbide whiskers in this embodiment is 350 nm, and the aspect ratio of the whiskers is 25.
[0124] The preparation method of the modified filler of this embodiment is:
[0125] S11: irradiating the silicon powder in a proton irradiation box for 7.5 minutes at an irradiation power of 370 W. After the irradiation, preheating the irradiated silicon powder at 57° C. for 10 minutes, and then heat-insulating the silicon powder to obtain pretreated silicon powder;
[0126] S12: adding the pretreated silicon powder to kaolin modification liquid which is 4 times the total amount of the pretreated silicon powder, stirring and modifying the liquid, after the stirring is completed, filtering and drying to obtain a modified filler.
[0127] The stirring speed of the stirring modification treatment in this embodiment is 600 r / min, and the stirring time is 50 min.
[0128] The preparation method of the kaolin modified liquid of this embodiment is:
[0129] 5.5 parts of kaolin and 2 parts of yttrium nitrate solution were added to 6.5 parts of sodium citrate solution, and then 2.5 parts of silane coupling agent KH550 and 3 parts of boron nitride were added, and the mixture was stirred and mixed to obtain a kaolin modified solution.
[0130] The mass fraction of the sodium citrate solution in this embodiment is 6.5%; the mass fraction of the yttrium nitrate solution is 3.5%.
[0131] The present embodiment provides an application of a method for preparing asphalt concrete in road paving.
[0132] Comparative Example 1.
[0133] The difference from Example 3 is that no strengthening agent is added.
[0134] Comparative Example 2.
[0135] The difference from Example 3 is that no stress treatment agent is added in the preparation of the strengthening agent.
[0136] Comparative Example 3.
[0137] The difference from Example 3 is that no whisker liquid is added to the treating agent.
[0138] Comparative Example 4.
[0139] The difference from Example 3 is that no sodium lignin sulfonate solution and lanthanum oxide are added to the treating agent.
[0140] Comparative Example 5.
[0141] The difference from Example 3 is that the whisker liquid is replaced by nano silicon carbide whiskers.
[0142] Comparative Example 6.
[0143] The difference from Example 3 is that no flaky talc liquid is added in the preparation of the strengthening agent.
[0144] Comparative Example 7.
[0145] The difference from Example 3 is that no modified filler is added.
[0146] Comparative Example 8.
[0147] The difference from Example 3 is that the S11 step is not used in the modified filler.
[0148] Comparative Example 9.
[0149] The difference from Example 3 is that the modified filler is not treated with kaolin modifying liquid.
[0150] Conventional tests were conducted to test the thermal conductivity, crack resistance and wear resistance of the products of Examples 1 to 3 and Comparative Examples 1 to 9. The test results are as follows:
[0151]
[0152]
[0153] It can be seen from Comparative Examples 1 to 9 and Examples 1 to 3 that;
[0154] The friction coefficient of the product of Example 3 is as high as 0.89, the splitting tensile strength is as high as 6.6 MPa, and the thermal conductivity is as high as 4.4 w / (mk). The product has excellent wear resistance, and the splitting tensile strength and thermal conductivity can be coordinated and improved;
[0155] The products of Examples 1-3 and Comparative Examples 1-9 were immersed in water for 24 hours, then frozen at -5°C for 12 hours, and finally placed at 65°C for 12 hours. The above is one cycle. The cycle test was repeated 10 times to test the water resistance, frost resistance and heat resistance stability of the products. The test results are as follows:
[0156]
[0157] It can be seen from Comparative Examples 1 to 9 and Example 3 that the product of Example 3 has excellent water resistance, frost resistance and heat resistance stability. At the same time, the product does not add any of the strength-enhancing agent and the modified filler, and the performance of the product deteriorates significantly. The synergistic effect of the two is the most significant.
[0158] The performance of the product tends to deteriorate when the stress treatment agent is not added in the preparation of the strength-enhancing agent, the whisker liquid is not added in the stress treatment agent, the sodium lignin sulfonate solution and lanthanum oxide are not added in the stress treatment agent, the whisker liquid is replaced by nano silicon carbide whiskers, and the flaky talc liquid is not added in the preparation of the strength-enhancing agent. The strength-enhancing agent obtained by using the specific whisker liquid and the stress treatment agent combined with the flaky talc liquid of the present invention has the most significant product performance effect, and the effect of using other methods instead is not as obvious as that of the present invention;
[0159] The modified filler was not treated with the S11 step and the modified filler was not treated with kaolin modification liquid. The performance of the product also showed a trend of deterioration to varying degrees. The performance of the product was more obviously deteriorated when the kaolin modification liquid was not used.
[0160] The preparation of kaolin modified liquid has a significant impact on the performance of the product, and further research is needed:
[0161] The preparation method of kaolin modified liquid is as follows:
[0162] 5.5 parts of kaolin and 2 parts of yttrium nitrate solution were added to 6.5 parts of sodium citrate solution, and then 2.5 parts of silane coupling agent KH550 and 3 parts of boron nitride were added, and the mixture was stirred and mixed to obtain a kaolin modified solution.
[0163] Take the product water resistance, frost resistance and heat resistance stability test as an example;
[0164] Experimental example 1.
[0165] The only difference from Example 3 is that no yttrium nitrate solution is added in the preparation of the kaolin modified solution.
[0166] Experimental example 2.
[0167] The only difference from Example 3 is that no kaolin is added in the preparation of the kaolin-modified liquid.
[0168] Experimental Example 3.
[0169] The only difference from Example 3 is that no boron nitride is added in the preparation of the kaolin modified solution.
[0170] Experimental Example 4.
[0171] The only difference from Example 3 is that no silane coupling agent KH550 is added in the preparation of the kaolin modified liquid.
[0172] Experimental Example 5.
[0173] The only difference from Example 3 is that the sodium citrate solution is replaced by water.
[0174]
[0175] It can be seen from Experimental Examples 1-5 that when kaolin is not added in the preparation of the kaolin-based modified liquid, the performance of the product has the greatest impact on the preparation of the kaolin-based modified liquid, followed by the absence of boron nitride, the absence of yttrium nitrate solution in the preparation of the kaolin-based modified liquid, the absence of silane coupling agent KH550 in the preparation of the kaolin-based modified liquid, and the sodium citrate solution is replaced by water. The performance of the products all tends to deteriorate. The kaolin-based modified liquid obtained by mutual coordination and synergy between the raw materials has the most significant effect on the product performance. The raw materials in the preparation of the kaolin-based modified liquid are indispensable, and the use of other methods to replace them is not as significant as the effect of the present invention.
[0176] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0177] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing asphalt concrete, characterized in that: The following steps are involved: Step 1: weigh the raw materials according to weight: Asphalt 35-40 parts, cement 25-30 parts, coarse aggregate 10-15 parts, strength-enhancing agent 9-12 parts, fine aggregate 8-14 parts, modified filler 5-8 parts, fly ash 4-6 parts, silane coupling agent 3-5 parts, deionized water 30-35 parts; Step 2, stirring and mixing the strengthening agent, modified filler, fly ash, silane coupling agent and deionized water at a speed of 450-550 r / min for 1-2 hours, and obtaining a mixed agent after the mixing is completed; Step three, asphalt, cement, coarse aggregate, fine aggregate and mixing agent are mixed at a temperature of 110-120° C. for 2-3 hours, and asphalt concrete is obtained after the mixing is completed.
2. The method for preparing asphalt concrete according to claim 1, characterized in that: The coarse aggregate is crushed stone with a particle size of 10 to 15 mm; the fine aggregate is fine sand with a particle size of 0.5 to 1.5 mm; The fly ash is Class I fly ash; and the silane coupling agent is silane coupling agent KH560.
3. The method for preparing asphalt concrete according to claim 1, characterized in that: The preparation method of the strengthening agent is as follows: S01: Stir and mix the flaky talc powder in a 5% potassium permanganate solution which is 3 to 5 times the total weight of the flaky talc powder, and then wash and dry; S02: mixing dry flaky talc powder, phosphate buffer solution and carboxymethyl cellulose in a weight ratio of (4-6):(2-5):2 to obtain a flaky talc liquid; S03: Emphasis on the preparation of treatment agents: The nano silicon carbide whiskers are mixed with a sufficient amount of sodium silicate solution to obtain a whisker solution, and 5 to 8 parts of the whisker solution, 3 to 5 parts of sodium lignin sulfonate solution, and 2 to 4 parts of lanthanum oxide are mixed and stirred to obtain a stress treatment agent; S04: Mix the flaky talc liquid and the strengthening agent in a weight ratio of 5:(2-3) and perform ball milling at a ball milling speed of 1000-1500r / min for 2h. After the ball milling is completed, wash with water and dry to obtain the strengthening agent.
4. The method for preparing asphalt concrete according to claim 3, characterized in that: The pH value of the phosphate buffer solution in S02 is 5.5; The mass fraction of the sodium silicate solution in S03 is 2-5%; the mass fraction of the sodium lignin sulfonate solution is 3-6%.
5. The method for preparing asphalt concrete according to claim 3, characterized in that: The average particle size of the nano silicon carbide whisker is 300-400nm, and the aspect ratio of the whisker is 20-30.
6. The method for preparing asphalt concrete according to claim 1, characterized in that: The preparation method of the modified filler is: S11: irradiating the silicon powder in a proton irradiation box for 5 to 10 minutes at an irradiation power of 350 to 400 W. After the irradiation, preheating the irradiated silicon powder at 55 to 60° C. for 10 minutes, and then heat-insulating the silicon powder to obtain pretreated silicon powder; S12: adding the pretreated silicon powder to kaolin modification liquid which is 3 to 5 times the total amount of the pretreated silicon powder, stirring and modifying the liquid, after the stirring is completed, filtering and drying to obtain a modified filler.
7. The method for preparing asphalt concrete according to claim 6, characterized in that: The stirring speed of the stirring modification treatment is 550-750 r / min, and the stirring time is 45-55 min.
8. The method for preparing asphalt concrete according to claim 6, characterized in that: The preparation method of kaolin modified liquid is as follows: Add 4 to 7 parts of kaolin and 1 to 3 parts of yttrium nitrate solution into 5 to 8 parts of sodium citrate solution, then add 2 to 3 parts of silane coupling agent KH550 and 2 to 4 parts of boron nitride, stir and mix thoroughly to obtain kaolin modified liquid.
9. The method for preparing asphalt concrete according to claim 8, characterized in that: The mass fraction of the sodium citrate solution is 5-8%; the mass fraction of the yttrium nitrate solution is 2-5%.
10. Use of the method for preparing asphalt concrete according to any one of claims 1 to 9 in road paving.
Citation Information
Patent Citations
Asphalt concrete and preparation process thereof
CN109293280A
Anti-cracking bituminous concrete and preparation technology thereof
CN109626876A
Water-permeable asphalt concrete as well as preparation method and application thereof
CN112358257A
High-temperature-resistant anti-rutting asphalt concrete and preparation method thereof
CN117247253A
Anaerobic adhesive composition and preparation method thereof
CN117903744A
Cited By
Pervious concrete reinforcing agent and preparation method thereof
CN120271268A
